Optimization of protease production from plant growth promoting Bacillus amyloliquefaciens showing antagonistic activity against phytopathogens - SUKANTA MAJUMDAR; USHA CHAKRABORTY (International Journal of Pharma and Bio Sciences, 2017)
Plant growth promoting rhizobacteria are the group of bacteria, which actively colonize plant root and exert beneficial effects on plant. They promote plant growth either by solubilizing inorganic phosphate, producing IAA or by inhibiting pathogens by producing variety of extracellular enzymes. An antagonistic bacterial strain with potent protease producing capacity was isolated from the jute rhizosphere. The isolate was identified as Bacillus amyloliquefaciens by means of 16S rDNA sequencing. Optimization study revealed that the optimum protease activity was 270.2 U/ml/min after 36 hours. The optimum temperature was found to be 40°C and optimum pH 8.5. Experiments with different carbon and nitrogen sources revealed fructose and yeast extract as the most favoured carbon and nitrogen. The isolate showed potent antagonistic activity against phytopathogens: Macrophomina phaseolina (61.5%) Fusarium oxysporum (82.6%) F. Semitectum (85.4%), Alternaria alternata (85.2%). Thus the isolate showed quite promising activity to be exploited as source of industrial production of protease as well as biocontrol agent.